SYSTEM APPLICATION OF ARTICLE 21 IN THE CALCULATIONS PPH BPKP JAKARTA USING MICROSOFT ACCESS - Ira Waruwu; Don Elsafitra, SKom (Jurnal Sistem Informasi, 2004)
In this paper the author tries to design a system of income tax calculation applicationArticle 21.Â The author hopes that this application systems can be used as onea reference for the computation of Income Tax Article 21.Â This application systemsystem is an additional application that can be used without having to changeexisting application systems.